Pengaruh Gadget Terhadap Perkembangan Sosial Emosional Anak Usia 5-6 Tahun Di TK Negeri Harapan Bangsa - Anggun Asri; Andi Agusniatih; Jane M Monepa; Shofiyanti Nur Zuama (Jurnal Pelita PAUD, 2025)
The problem in this research lies in the social emotional development of children. This study aims to determine the effect of gadget use on social emotional development. The research method used in this study is a correlational quantitative approach. The subjects of this study were 28 children consisting of 14 girls and 14 boys in the even semester of 2024/2025. Data collection techniques through observation, questionnaires, and documentation. Data analysis techniques were carried out by testing the normality of the data. The normality test in this study used the Kolmogorov Smirnov test to determine whether the data was normally distributed or not. homogeneity test. The homogeneity test in this study used the Levene test technique which is used to test the variance of more than two groups of data and is an alternative to the Barlett test. Hypothesis testing used a simple linear regression test consisting of the F test (simultaneous), r test (correlation coefficient) using SPSS. The test result was 0.381. Then, we continue by looking at the coefficient value of "r" product moment of 28 with a significance level of 5% is 0.374 which means it is greater than 0.381 0.374. This figure indicates that the working hypothesis (Hâ‚’) in this study is accepted, namely there is an influence of gadget use on the social emotional development of children aged 5-6 years at Harapan Bangsa State Kindergarten. Meanwhile, the null hypothesis (Hâ‚) is rejected.